Increasing The Influence Of Product Quality And Price Perception On Purchase Decisions: The Mediating Role of Social Media Interaction (Case Study at Bubble Teahouse Chain Outlet) - Cahya Eka Prasetyo; Parlagutan Silitonga; Etty Nurwati (Eduturisma, 2023)
This study investigates the role of social media interaction in mediating the relationship between product quality and price perception on purchase decisions at Bubble Teahouse Chain outlet. The questionnaire was distributed to customers using an accidental sampling technique with a final sample size of 120 respondents. This research hypothesis test used Smart PLS 3.0. The results revealed that product quality had significantly influenced social media interaction, and price perception had significantly influenced purchase decisions. However, product quality had no significant influence on purchase decisions, price perception had no significant influence on social media interaction, and social media interaction had no significant influence on purchase decisions. With the addition of the social media interaction variable as an intervening variable between product quality and purchase decision, it gave different results and showed that product quality had a significant influence on purchase decision. These key findings revealed that social media interaction can increase the influence of product quality and price perception on purchase decisions. The managerial implication of this result was that social media interaction became an effective tool to enhance the marketing strategy, increase purchase decisions, and then sales performance.